Mnk2 Alternative Splicing Modulates the p38-MAPK Pathway and Impacts Ras-Induced Transformation - Avraham Maimon; Maxim Mogilevsky; Asaf Shilo; Regina Golan-Gerstl; Akram Obiedat; Vered Ben-Hur; Ilana Lebenthal-Loinger; Ilan Stein; Reuven Reich; Jonah Beenstock; Eldar Zehorai; Claus L. Andersen; et al. (Cell Reports, 2014)
Summary: The kinase Mnk2 is a substrate of the MAPK pathway and phosphorylates the translation initiation factor eIF4E. In humans, MKNK2, the gene encoding for Mnk2, is alternatively spliced yielding two splicing isoforms with differing last exons: Mnk2a, which contains a MAPK-binding domain, and Mnk2b, which lacks it. We found that the Mnk2a isoform is downregulated in breast, lung, and colon tumors and is tumor suppressive. Mnk2a directly interacts with, phosphorylates, activates, and translocates p38α-MAPK into the nucleus, leading to activation of its target genes, increasing cell death and suppression of Ras-induced transformation. Alternatively, Mnk2b is pro-oncogenic and does not activate p38-MAPK, while still enhancing eIF4E phosphorylation. We further show that Mnk2a colocalization with p38α-MAPK in the nucleus is both required and sufficient for its tumor-suppressive activity. Thus, Mnk2a downregulation by alternative splicing is a tumor suppressor mechanism that is lost in some breast, lung, and colon tumors. : The Mnk2 kinase is a MAPK pathway substrate and phosphorylates the translation initiation factor eIF4E. Mnk2 is alternatively spliced yielding two isoforms: Mnk2a and Mnk2b. Maimon et al. now report that Mnk2a is downregulated in many tumors and behaves like a tumor suppressor. They show that whereas Mnk2b is pro-oncogenic and does not activate p38α-MAPK, Mnk2a phosphorylates and activates p38α-MAPK leading to induction of its target genes, cell death, and suppression of Ras-induced transformation.